Elementy procesu zarządzania rozwojem pracowników w firmach międzynarodowych - Suchodolski, Adam (Elements of employee' development management in international companies, 2006)
The main goal of the article is to present and evaluate the elements of managing employees’ development in international companies operating in Poland. The issue of managing employee development is analyzed from the viewpoint of an organized cycle. The research data being presented refer to three phases of development management, i.e. preparation, realization and control. The phenomena under study cover 18 organizations in which the empirical research on personnel function has been completed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 291-298